Comparison of nasal and olfactory functions between two surgical approaches for the treatment of concha bullosa: a randomised clinical trial. Issue 10 (30th September 2019) - Andaloro, C; La Mantia, I; Castro, V; Grillo, C
Abstract: Objective: Concha bullosa may be associated with paranasal sinus infections and nasal obstruction. Middle concha mucosa membranes have olfactory neurofibrils. This study investigated the impact of routinely used concha bullosa surgery techniques – crushing and lateral laminectomy – on nasal and olfactory functions. Methods: Forty-three adult patients who had undergone surgery for a symptomatic concha bullosa completed the odour test, nasal obstruction visual analogue scale, 22-item Sino-Nasal Outcome Test, and peak nasal inspiratory flow test, pre-operatively and three months post-operatively. The pre- and post-operative results within and between the two treatment groups were compared. Results: Intragroup comparison of mean pre- versus post-treatment changes revealed statistically significant findings for the nasal obstruction visual analogue scale, Sino-Nasal Outcome Test, peak nasal inspiratory flow and olfaction tests (all p < 0.05). However, there were no statistically significant changes when comparing the scores between the groups (intergroup comparison). Conclusion: Lateral laminectomy and crushing in concha bullosa surgery have no negative effects on olfactory function. Concha bullosa surgery provides positive outcomes regarding nasal complaints in symptomatic patients.